Pharmacokinetic study of the combination of tacrolimus and fluconazole in renal transplant patients. - Dusit Lumlertgul (2018)
BACKGROUND: It was hypothesized that fluconazole in combination with tacrolimus can be used safely with an imitated area under curve (AUC) compared to tacrolimus. At every time point, this combination was presumed to correlate well with pre-intervention AUC, thus the dosage could be significantly reduced. MATERIAL AND METHOD: There were two groups of patients. Group I (n = 15) included patients who received tacrolimus at 0.1-0.3 mg/kg/day within one week after transplantation. These patients were studied for tacrolimus whole blood concentrations. The tacrolimus dosage was then reduced by 40% and given in combination with fluconazole at 100-200 mg/day for one week, tacrolimus whole blood concentrations were studied again. Group II (n = 8) included patients who had been transplanted for more than 3 months and had received a stable dosage of tacrolimus in combination with fluconazole for at least one month. RESULTS: In group I, before fluconazole combination, trough levels correlated well with AUC0-12. After fluconazole combination, trough levels still correlated well with AUC0-12. The after/before fluconazole-combination ratio of AUC0-12 and maximum tacrolimus concentration (Cmax) was 1.08 (90%CI; 0.98-1.19) and 1.17 (90%CI; 1.00-1.36), respectively. Correspondingly, the oral bioavailability, which was the after/ before fluconazole combination ratio of AUC0-12/dose and absorption rate (Cmax/dose/body weight), was significantly increased [2.08 (90%CI; 1.80-2.40) and 2.24 (90%CI; 1.99-2.51), respectively]. Tacrolimus clearance after the fluconazole combination was significantly reduced, compared with before the combination (14.74 vs 38.79 L/h, p = 0.001). Mean tacrolimus dosage in this group could be reduced from 10.7 mg/day before fluconazole combination to 5.7 mg/day after it and to 3.7 mg/day at 3 months after transplantation (p = 0.001). In group II, trough levels correlated well with AUC0-12 and the mean tacrolimus dosage in this group was only 2.9 mg/day. CONCLUSION: This present study showed a good correlation between tacrolimus trough levels and AUC, which occurred in monotherapy or in patients who received fluconazole. The tacrolimus trough levels could be trusted in monitoring patients who received a tacrolimus-based immunosuppressive regimen. The combination to fluconazole was ascertained and it was safe to reduce the dose of tacrolimus.